Note: Ranking DMUs with Infeasible Super-Efficiency DEA Models - Xue, Mei; Harker, Patrick T. (Management Science, 2002)
It has been suggested in the data envelopment analysis (DEA) literature that it is impossible to obtain a full ranking of decision-making units (DMUs) when infeasible subproblems arise in the so-called super-efficiency DEA models under different returns to scale (RTS) assumptions other than constant returns to scale (CRS) andconsequently the application of the super-efficiency DEA models under different RTS conditions other than CRS should be restricted. The implications of the infeasibility in super-efficiency DEA models with respect to the efficiency ranking of the DMUs is explored. Based on the analysis, we show that it is still possible to obtain the full ranking of the entire observation set when infeasibilities arise in super-efficiency DEA models.